PENGARUH TEKNIK RELAKSASI TERHADAP KECEMASAN AKADEMIK MAHASISWA SEMESTER 8 PROGRAM STUDI BIMBINGAN KONSELING MELALUI KONSELING KELOMPOK DI UNIVERSITAS RIAU - Pilijaya, Lasmaria; Yakub, Elni; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of relaxation techniques on academic anxiety in the 8th semester students of the Counseling Study Program through group counseling at the University of Riau. This type of research is a quantitative study with an experimental method using the research design One-Group Pretest-Posttest Design. The measuring instrument used in this study is the academic anxiety scale consisting of 50 items before the validity, and after the validity is obtained valid items number 32 items with validity of 0,531 and reliability of 0,890. The subjects of this study were 7 students in the 8th semester of the Guidance Counseling Study Program who were identified as having academic anxiety. The data analysis technique used is non-parametric statistical techniques using the Wilcoxon test. The results of the study proved that the research hypothesis was accepted. For this reason, it can be concluded that there are differences in behavior scores off task before and after being given treatment in the form of relaxation techniques. From the results of the spearmen rank test it was obtained 0.008 while the correlation coefficient of was 0.883, thus there was an effect of 78% on academic anxiety of 8th semester students in the Counseling Study Program through group counseling at the University of Riau.Key Words: Relaxation, Students Academic Anxiety